Design and analysis of a magneto-rheological damper for an all terrain vehicle - Krishnan Unni, R; Tamilarasan, N. (IOP conference series. Materials Science and Engineering, 2018)
A shock absorber design intended to replace the existing conventional shock absorber with a controllable system using a Magneto-rheological damper is introduced for an All Terrain Vehicle (ATV) that was designed for Baja SAE competitions. Suspensions are a vital part of an All Terrain Vehicles as it endures various surfaces and requires utmost attention while designing. COMSOL multi-physics software is used for applications that have coupled physics problems and is a unique tool that is used for the designing and analysis phase of the Magneto-rheological damper for the considered application and the model is optimized based on Taguchi using DOE software. The magneto-rheological damper is designed to maximize the damping force with the measured geometric constraints for the All Terrain Vehicle.